2021
DOI: 10.3390/antiox10091368
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins and Functional Compounds Change in a Third-Generation Snacks Prepared Using Extruded Blue Maize, Black Bean, and Chard: An Optimization

Abstract: The effect of extrusion cooking on bioactive compounds in third-generation snacks (TGSE) and microwave-expanded snacks (MWSE) prepared using black bean, blue maize, and chard (FBCS) was evaluated. FBCS was extruded at different moisture contents (MC; 22.2–35.7%), extrusion temperatures (ET; 102–142 °C), and screw speeds (SP; 96–171 rpm). Total anthocyanin content (TAC), contents of individual anthocyanins, viz., cyanidin-3-glucoside, malvidin-3-glucoside, pelargonidin-3-glucoside, pelargonidin-3-5-diglucoside,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
(134 reference statements)
2
6
0
Order By: Relevance
“…Specifically, they reported values of 966.32 mg FE/100 g dw for finger millet and 506.71 mg FE/100 g dw for sorghum. This observation aligns with the conclusions drawn by other researchers, including Neder-Suárez et al [45], Escalante-Aburto et al [46], and Menchaca-Armenta et al [47] who similarly identified the impact of processing parameters on the anthocyanin content in nixtamalized blue corn flour.…”
Section: Difference Between Htst Process and Ltlt Processsupporting
confidence: 92%
“…Specifically, they reported values of 966.32 mg FE/100 g dw for finger millet and 506.71 mg FE/100 g dw for sorghum. This observation aligns with the conclusions drawn by other researchers, including Neder-Suárez et al [45], Escalante-Aburto et al [46], and Menchaca-Armenta et al [47] who similarly identified the impact of processing parameters on the anthocyanin content in nixtamalized blue corn flour.…”
Section: Difference Between Htst Process and Ltlt Processsupporting
confidence: 92%
“…Chroma gives further information on the saturation or intensity of color. A confounding phenomenon regarding chroma is that it will increase with pigment concentration to a maximum and then decreases as the color darkens [24]. In the high ratio of solvent to sample (20:1) used in this experiment with the low concentration of the pigments, chroma should increase with pigment concentration.…”
Section: Color Parametersmentioning
confidence: 99%
“…Chroma gives further information on the saturation or intensity of color. A confounding phenomenon regarding chroma is that it will increase with pigment concentration to a maximum and then decreases as the color darkens [24]. In the high ratio of [7]), ( 4) ethanol (Karaaslan & Yaman 2017 [12]), ( 5) chloroform: methanol (Clf:MeOH, Solovchenko et al [6]), ( 6) acetone (Garcia-Viguera et al [17]), ( 7) water (Karaaslan & Yaman [12]), ( 8) pH differential buffers (Lee et al [11]), (9) combined solvents (methanol: water and followed by pH differential; Gauch et al [16]).…”
Section: Color Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in our experiment with different extraction buffers and three sample types (fresh, frozen and freeze-dried), Delphinidin (25) was the main anthocyanin, present in all extraction methods and sample types. Neder-Suárez [39] expressed that extraction methods significantly affect Cyanidin-3-glucoside content and could similarly affect other anthocyanins. Ghassempour et al [18] also discovered that different extraction methods (organic solvent, ultrasound and microwave assisted) extracted different anthocyanin profiles from grape skin in their experiment.…”
Section: Uhplc Profiling Of Individual Anthocyaninsmentioning
confidence: 99%